Positive association between blood ethylene oxide levels and metabolic syndrome: NHANES 2013-2020 - Zhou, Chunqi; Wang, Senlin; Ju, Lingling; Zhang, Ruimin; Yang, Yunning; Liu, Yanjun (Frontiers in Endocrinology, 2024)
The exposure of Ethylene oxide (EO) is linked to systemic inflammatory response and various cardiovascular risk factors. Hemoglobin's binding to ethylene oxide (HbEO) was used to measure serum EO level. This research aims to explore the association between metabolic syndrome (MetS) and HbEO, and between HbEO and components of metabolic syndrome. This research included 1842 participants from 2013 to 2020 in National Health and Nutrition Examination Survey (NHANES) database. Weighted logistic regression models were used to analyze the relationship between HbEO and metabolic syndrome risk, using odds ratio (OR) and 95% confidence interval (CI). The restricted cubic spline plot explores whether there is a dose-response relationship between HbEO and MetS risk. Subgroup analysis was performed to analyze study heterogeneity. Significant differences were found in gender, educational level, marital status, diabetes status and hypertension among different groups (P < 0.001, P = 0.007, P = 0.003, P < 0.001, P < 0.001, respectively). The serum HbEO level exhibited positive correlation with metabolic syndrome risk in Q2 level (OR=1.64, 1.04~2.48), Q3 level (OR=1.99, 1.29~3.08), and Q4 level (OR=2.89, 1.92~4.34). The dose-response association suggested a possible linear association between serum HbEO and metabolic syndrome risk (P-overall=0.0359, P-non-linear=0.179). L-shaped association was found between HbEO and the risk of MetS in female population, obese population and mid-age and elder population (P-overall<0.001, P-non-linear=0.0024; P-overall=0.0107, P-non-linear=0.0055 P-overall<0.001 P-non-linear=0.0157). This study indicates a linear correlation between MetS and HbEO, with MetS risk escalating as HbEO levels increase. The prevalence of MetS varies depending on BMI, age and gender, and these factors can also influence MetS prevalence when exposed to EO.